Noninvasive reconstruction of placental methylome from maternal plasma DNA: Potential for prenatal testing and monitoring. - Sun, Kun; Lun, Fiona M. F.; Leung, Tak Y.; Chiu, Rossa W. K.; Lo, Y. M. Dennis; Sun, Hao (Prenatal Diagnosis, 2018)
Objective: During human pregnancy, the DNA methylation of placental tissue is highly relevant to the normal growth and development of the fetus; therefore, methylomic analysis of the placental tissue possesses high research and clinical value in prenatal testing and monitoring. Thus, our aim is to develop an approach for reconstruction of the placental methylome, which should be completely noninvasive and achieve high accuracy and resolution.Results: We propose a novel size-based algorithm, FEtal MEthylome Reconstructor (FEMER), to noninvasively reconstruct the placental methylome by genomewide bisulfite sequencing and size-based analysis of maternal plasma DNA. By applying FEMER on a real clinical dataset, we demonstrate that FEMER achieves both high accuracy and resolution, thus provides a high-quality view of the placental methylome from maternal plasma DNA. FEtal MEthylome Reconstructor could also predict the DNA methylation profile of CpG islands with high accuracy, thus shows potential in monitoring of key genes involved in placental/fetal development. Source code and testing datasets for FEMER are available at http://sunlab.cpy.cuhk.edu.hk/FEMER/.Conclusion: FEtal MEthylome Reconstructor could enhance the noninvasive fetal/placental methylomic analysis and facilitate its application in prenatal testing and monitoring.